Incorporation of Databases for Faster Meta Search Engine (International Journal of Advanced Research in Computer Science, 2017)
A meta search engine is a kind of tool that combines results of multiple individual search engines by sending queries to them. In existing meta search engine, there is no concept of database of meta search engine. Common search engines have their own database. For faster communication and efficiency purpose, database concept should be used with meta search engine. This paper discusses the model of database for meta search engine.Keywords: meta search engine; database; updating, efficiency; communication